Strategi penanaman karakter Cinta Tanah Air melalui kegiatan kepesantrenan di Pondok Pesantren Al Khair Wal Barokah - Dewi Anggraeni; Silvi Maharani (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
The influence of foreign culture and globalization has made the younger generation less understanding and appreciative of the values of nationalism. Therefore, pesantren education as the oldest educational institution in Indonesia, has a strategic role in shaping the character of students who are noble and have a strong sense of patriotism. Research data shows that the sense of love for the country is currently experiencing a decline, especially among students. This can be seen from almost some Indonesian students who only memorize Pancasila. To overcome this challenge, a strategy is needed to instill the character of patriotism. This study aims to describe boarding activities at Al Khair Wal Barokah Islamic Boarding School and analyze the strategies used in instilling the character of love for the country to students. This research uses interviews, observations and documentation studies as data collection methods, followed by critical and reflective analysis. The findings of this study reveal that the organized boarding activities are closely related to nationalism. The strategy in instilling the character of love for the homeland for students at Al Khair Wal Barokah Islamic Boarding School is carried out through national commitment which is realized through flag ceremonies, exemplary pesantren caregivers, and local identity through the use of batik which reflects pride in cultural heritage.